Evaluating the Effectiveness of the National Curriculum and Training Institute’s “Cognitive Life Skills” Program among Parolees Supervised by Pennsylvania’s Board of Probation & Parole - Antonio, Michael E. (American journal of criminal justice, 2017)
Recently, cognitive-behavioral approaches for rehabilitation have shown measured success for reducing recidivism rates among offenders after release from prison. The present analysis utilized data provided by Pennsylvania’s Board of Probation & Parole about offenders who completed the Cognitive Life Skills program developed by the National Curriculum and Training Institute. Propensity scoring techniques were employed to match a group of offenders who completed the program (treatment) with a statistically equivalent group who did not receive it (control). Matching variables included location and year of release, risk level, gender, age, race, offense category, and history of violent offending. General findings from a Cox proportional hazard model revealed gender, age, and criminal history impacted future incidents of recidivism, measured as re-incarceration. More importantly, the hazard model revealed, on average, a 24 % reduction in recidivism among the treatment group offenders and, on average, a 31 % reduction among high risk offenders exclusively. Policy implications will be discussed.